Knowledge Science, Engineering and Management : 8th International Conference, KSEM 2015, Chongqing, China, October 28-30, 2015, Proceedings - Zhang, Songmao; Wirsing, Martin; Zhang, Zili.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Knowledge Science, Engineering and Management, KSEM 2015, held in Chongqing, China, in October 2015. The 57 revised full papers presented together with 22 short papers and 5 keynotes were carefully selected and reviewed from 247 submissions. The papers are organized in topical sections on formal reasoning and ontologies; knowledge management and concept analysis; knowledge discovery and recognition methods; text mining and analysis; recommendation algorithms and systems; machine learning algorithms; detection methods and analysis; classification and clustering; mobile data analytics and knowledge management; bioinformatics and computational biology; and evidence theory and its application.
Formal reasoning and ontologies -- Knowledge management and concept analysis -- Knowledge discovery and recognition methods -- Text mining and analysis -- Recommendation algorithms and systems -- Machine learning algorithms -- Detection methods and analysis -- Classification and clustering -- Mobile data analytics and knowledge management -- Bioinformatics and computational biology -- Evidence theory and its application.
Keywords: Computer vision; Artificial intelligence; Optical pattern recognition; Computer graphics; Computer Communication Networks; Computer software; Image Processing and Computer Vision; Artificial Intelligence; Pattern Recognition; Computer Graphics; Computer Communication Networks; Algorithm Analysis and Problem Complexity